«Pepper’s patches» on Rangifer pelage - Pruitt, Jr., William O.; Pepper, Hubert (Rangifer, 1986)
We describe and give frequencies of occurrence of a rarely-mentioned pattern of spots in Rangifer pelage. We also show that the pattern was well-known to Palaeolithic humans who recorded it in their cave art. We also discuss some of the symbolic possibilities resulting from the recognition by Palaeolithic humans of the biological characteristics of the pattern in Rangifer.